Surfing the complex interaction between new technology and norms: A resistance or resilience issue? Insights by the Viable System Approach (VSA) - Barile, Sergio; Simone, Cristina; La Sala, Antonio; Conti, Marcelo Enrique (Acta Europeana Systemica, 2020)
The paper investigates the complex interaction between technological innovation and norms: a crucial dynamic to facing the severe challenges of the Anthropocene. On the one hand, the sedimentation of norms acts as the genetic memory of a society. Allowing a reduction in the uncertainty of human condition and ensuring greater predictability of human interaction, the set of norms tend to activate a system of constraints that normalize and legitimate technological innovations. On the other hand, technological innovation is one of the most unpredictable and non-linear sources of change. It demands legitimization for what in the past were excluded or prohibited a priori (e.g. behaviors, ethics): this may trigger a “decoupling” process from the extant set of norms. Nevertheless, what decoupling should be legitimized? A wicked problem arises, and forking paths emerge in the socio-economic landscape. Leading the tension between new technology (source of unpredictability) and the taken-for-granted norms (source of predictability) is crucial if the aim is to linking effectiveness and efficiency to viable sustainability. While the (still dominant) cartesian approach considers norms and new technology as separate elements of the social system, system thinking enlightens the interaction between them. This helps to unveil hidden options/feedbacks in the decoupling-recoupling process between technological innovation and the evolution of norms enriching the information variety of the decision-makers (policy makers, citizens, urban planners, etc.). The dynamics that govern this dyad, however, are not linear: norms, in fact, do not have the same reactivity to absorb (recouple) the change triggered by new technologies (decoupling from the extant set of norms). Although the relevance of the issue, it has been often neglected, or at least not taken in the right consideration. Therefore, aiming to investigate this dyadic relationship, the paper focuses on the ambiguous role technology plays in enabling resilience: sometimes it acts as a resilience amplifier; sometimes it is a resilience inhibitor (and even a steel cage); sometimes it provokes an undesirable deviation from the taken-for-granted codified rules. In particular, aiming to contribute in filling this gap, and rooting in the Viable System Approach (VSA), the paper investigates why and how in some cases the interaction between technological innovation and norms leads to resistance towards change or acts as a resilience amplifier in other cases. The paper is structured as follows: after an Introduction underlying the need to understanding the increasing tension between new technology and norms, Section 2 deals with the contribution of the VSA in understanding the social systems; then, rooting in the VSA and moving from the concept of information variety, Section 3 frames the complex interplay between new technology and taken-for-granted norms as one of the most dramatic “resistance-resilience” issue of the Anthropocene era; Section 4 proposes a more comprehensive framework discussing the range “resilience-resistance-vulnerability” and presents final reflections.